2018
DOI: 10.1016/j.tins.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

ER Proteostasis Control of Neuronal Physiology and Synaptic Function

Abstract: Neuronal proteostasis is maintained by the dynamic integration of different processes that regulate the synthesis, folding, quality control, and localization of proteins. The endoplasmic reticulum (ER) serves as a fundamental pillar of the proteostasis network, and is emerging as a key compartment to sustain normal brain function. The unfolded protein response (UPR), the main mechanism that copes with ER stress, plays a central role in the quality control of many ion channels and receptors, in addition to cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 130 publications
2
94
0
Order By: Relevance
“…Surprisingly, overexpression of XBP1s in the hippocampus did not result in clear upregulation of canonical UPR target genes described in other tissues. This is in agreement with recent findings suggesting that the UPR, and more specifically XBP1, has alternative functions in the nervous system, directly controlling synaptic plasticity (32). Importantly, the appearance of senescent cells, which is associated with age-mediated loss of brain function (33), was prevented by XBP1s overexpression, whereas IRE1α deficiency accelerated the accumulation of senescent cells, suggesting that the UPR exerts global effects in sustaining the health of brain tissue during aging.…”
supporting
confidence: 92%
“…Surprisingly, overexpression of XBP1s in the hippocampus did not result in clear upregulation of canonical UPR target genes described in other tissues. This is in agreement with recent findings suggesting that the UPR, and more specifically XBP1, has alternative functions in the nervous system, directly controlling synaptic plasticity (32). Importantly, the appearance of senescent cells, which is associated with age-mediated loss of brain function (33), was prevented by XBP1s overexpression, whereas IRE1α deficiency accelerated the accumulation of senescent cells, suggesting that the UPR exerts global effects in sustaining the health of brain tissue during aging.…”
supporting
confidence: 92%
“…Because the proteostasis network (including chaperones, degradation factors, and trafficking factors) plays an essential role in controlling the biogenesis of membrane proteins, we evaluated how loss of LMAN1 affects the proteostasis network in the central nervous system [28,29]. It was previously reported that in Lman1−/− mouse liver, the total protein level of GRP78 increased substantially without significant induction of the unfolded protein response (UPR) genes, including Grp78, Grp94, Xbp1, Chop and Atf4 [27].…”
Section: Influence Of Lman1 Knockout On the Proteostasis Network In Tmentioning
confidence: 99%
“…The observations on cell-nonautonomous control of the HSR extend to the UPR ER and the UPR MT (Durieux et al 2011;Imanikia et al 2018;Martínez et al 2018;Zhang et al 2018). Perturbation of the mitochondrial electron transfer chain increases life span in both invertebrates and rodents through the activation of the UPR MT (Liu et al 2005;Copeland et al 2009;Durieux et al 2011).…”
Section: Cell-nonautonomous Regulation Of Organismal Proteostasismentioning
confidence: 99%